THE USE OF MINERAL AND ORGANIC SOIL CONDITIONER TO IMPROVE SOIL QUALITY OF TYPIC KANHAPLUDULTS TAMANBOGO, LAMPUNG - DARIAH, AI; SUTONO, .; NURIDA, NENENG LAILA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2010)
As soil conditioner, there are many functions of organic matter that would not be replaced by mineral material. Therefore, mineral soil conditioner is better focused on increasing quality of organic soil conditioner. The objective of the research was to obtain the effectiveness of soil conditioner formula (organic matter and zeolit) and its application technique (dose and phase application) in improving soil quality. The research was conducted at KP Tamanbogo, Lampung for three seasons (2006/2007). The experiment employed a split plot design with three reflications. Application techniques of soil conditioner (dose and phase aplication) as main plots and three types formula of soil conditioner as sub plots. Corn was used as test crop. Parameters observed were plant growth and production, and changes in soil properties. The results showed that soil conditioner that applied on Typic kanhapludults could significantly increased corn growth and yield. Soil conditioner with higher organic matter proportion has better effect on corn growth and yield as well as on physical soil properties, which indicated by soil permeability and aggregate stability. The addition of 20% of zeolit in soil conditioner formula increased soil microorganism activities, but the additional up to 30% decrease microorganism activities. The changes of organic matter and zeolit proportion in soil conditioner has significantly effect on soil pH and N content, but has no significantly effect on P, K content, and CEC. Compared to innitial soil condition, application of soil conditioner could increase CEC from <4 cmolc kg-1 to 5.85 cmolc kg-1 respectively. Soil conditioner was better to be applied periodically but must be done every season. For degraded soil such as at KP. Tamanbogo, soil conditioner was applied with 10 t ha-1 dose for innitial rehabilitation process, hereinafter with 5 t ha-1 annual crop season dose.